Counselling on and women's awareness of pregnancy danger signs in selected rural health facilities in Burkina Faso, Ghana and Tanzania - Duysburgh, Els; Yé, Maurice; Williams, Afua; Massawe, Siriel; Sié, Ali; Williams, John; Mpembeni, Rose; Loukanova, Svetla; Temmerman, Marleen (Tropical medicine & international health, 2013)
Objective The aims of this study were to (i) assess healthcare workers' counselling practices concerning danger signs during antenatal consultations in rural primary healthcare (PHC) facilities in Burkina Faso, Ghana and Tanzania; to (ii) assess pregnant women's awareness of these danger signs; and (iii) to identify factors affecting counselling practices and women's awareness. Methods Cross-sectional study in rural PHC facilities in Burkina Faso, Ghana and Tanzania. In each country, 12 facilities were randomly selected. WHO guidelines were used as standard for good counselling. We assessed providers' counselling practice on seven danger signs through direct observation study (35 observations/facility). Exit interviews (63 interviews/facility) were used to assess women's awareness of the same seven danger signs. We used negative binomial regression to assess associations with health services' and socio-demographic characteristics and to estimate per study site the average number of danger signs on which counselling was provided and the average number of danger signs mentioned by women. Results About one in three women was not informed of any danger sign. For most danger signs, fewer than half of the women were counselled. Vaginal bleeding and severe abdominal pain were the signs most counselled on (between 52% and 66%). At study facilities in Burkina Faso, 58% of the pregnant women were not able to mention a danger sign, in Ghana this was 22% and in Tanzania 30%. Fever, vaginal bleeding and severe abdominal pain were the danger signs most frequently mentioned. The type of health worker (depending on the training they received) was significantly associated with counselling practices. Depending on the study site, characteristics significantly associated with awareness of signs were women's age, gestational age, gravidity and educational level. Conclusion Counselling practice is poor and not very efficient. A new approach of informing pregnant women on danger signs is needed. However, as effects of antenatal care education remain largely unknown, it is very well possible that improved counselling will not affect maternal and newborn mortality and morbidity.
Gesehen am 07.01.2021